Bicarbonate effects, electromotive forces and potassium effluxes in rabbit and guinea-pig gall-bladder. - Cremaschi, D (1983)
The stimulating effect of external HCO3- on Na+ salt transport has been examined in rabbit and guinea-pig gall-bladder by electrophysiological methods, as a sequel to a previous study carried out by radiochemical techniques. At steady state, cell K+ activity was found to be significantly reduced in the presence of HCO3-, whereas cell Na+ activity significantly increased; in parallel the apical membrane p.d. was depolarized; K+ equilibrium potential was higher than membrane p.d. in every case. The apical p.d. dependence on K+ was unaffected by HCO3-, but in the guinea-pig it was affected by Cl-. Rapid increases in HCO3- concentration on the luminal side caused a depolarization of the apical p.d. of the guinea-pig within about 30 sec, an effect that did not occur if the tissue was pre-treated with 10(-4) M-acetazolamide; the epithelial resistance and apical/basolateral resistance ratio were unchanged in all cases. The primary action of HCO3- is confirmed to be on the apical membrane; an HCO3- conductance does not seem to be present at this level, either in the rabbit or guinea-pig, nor does HCO3- affect Na+ influx through the apical conductive pathway, so that all the stimulating effects of the anion are confirmed to be on the neutral transports of Na+ salts; in spite of this, the apical electromotive force is modified due to the changed cell K+ activity. The rapid depolarization caused by the anion in the guinea-pig is in agreement with an HCO3- electrogenic secretion and/or a basolateral conductance for the anion. Polyelectrolyte dissociation from protons increases in the absence of external HCO3-: the negative charges are mainly counterbalanced by bound Na+ in the rabbit and by free K+ in the guinea-pig. K+ leakage from the cell into the lumen is calculated to be minimal in the rabbit and all K+ lost could be reabsorbed through the paracellular pathways; K+ efflux to the subepithelial layer via conductive routes is insufficient to account for the over-all K+ efflux.